INTERNATIONAL STOCK MARKET COMOVEMENT AND NEWS. (December 2014) - Höchstötter, Markus; Meyer, Stephan; Riordan, Ryan; Storkenmaier, Andreas
Abstract We explore how news comovement drives a portion of stock return comovement using the Thomson Reuters international business news database. We develop a measure of news comovement similar in design to a well‐known measure of stock return comovement and find that news helps explain country‐level stock market comovement. Our results are novel in that we find that more news comovement is related to higher stock market comovement. The explanatory power of news comovement is found to be particularly strong in countries that have low total market capitalization, are more corrupt, and have lower accounting standards.